Options on Leveraged Equity: Theory and Empirical Tests - Toft, Klaus Bjerre; Prucyk, Brian (Journal of Finance, 1997)
We develop an option pricing model for calls and puts written on leveraged equity in an economy with corporate taxes and bankruptcy costs. The model explains implied Black-Scholes volatility biases by relating them to the firm's structural characteristics such as leverage and debt covenants. We test the model by comparing predicted pricing biases with biases observed in a large cross-section of firms with liquid exchange traded option contracts. Our empirical study detects leverage related pricing biases. The magnitudes of these biases correspond to those predicted by our model. We also find significant pricing biases for firms financed primarily by short-term debt. This supports our model because short-term debt introduces net-worth hurdles similar to net-worth covenants.